ANALISIS FAKTOR INTERNAL YANG MEMPENGARUHI KINERJA GURU (STUDI KASUS GURU SMP SWASTA KOTA JUANG KABUPATEN BIREUEN) - Mawardi, Mawardi; Iskandar, Raihan; Muttaqim, Hakim (LPPM-UNIKI, 2023)
The research was conducted using a quantitative descriptive method in assessing the internal factors that affect teacher performance. The factors studied were limited to 3 (three) things, namely the level of education, teacher competence and teaching experience. Study of teachers working in private junior high schools in Juang City, Bireuen Regency. Alleged research, there is a direct influence from the causality of the three observed exogenous variables on the endogenous variable